Major bleeding with vitamin K antagonists or direct oral anticoagulants in real-life. (15th January 2017) - Becattini, Cecilia; Franco, Laura; Beyer-Westendorf, Jan; Masotti, Luca; Nitti, Cinzia; Vanni, Simone; Manina, Giorgia; Cattinelli, Sergio; Cappelli, Roberto; Sbrojavacca, Rodolfo; Pomero, Fulvio; Marten, Sandra; et al.
Abstract: Background: Limited data are available on major bleeding (MB) occurring during treatment with vitamin K (VKAs) or direct oral anticoagulants (DOACs) outside clinical trials. Methods: Patients hospitalized for MB while on treatment with VKAs or DOACs were included in a multicenter study to compare clinical presentation, management and outcome of bleeding. The primary study outcome was death at 30 days. Results: Between September 2013 and September 2015, 806 patients were included in the study, 76% on VKAs and 24% on DOACs. MB was an intracranial hemorrhage in 51% and 21% patients on VKAs or DOACs, respectively (Odds Ratio [OR] 3.79; 95% confidence interval [CI] 2.59–5.54) a gastrointestinal bleeding in 46% and 25% patients on DOACs and VKAs, respectively (OR 2.62; 95% CI 1.87–3.68). Death at 30 days occurred in 130 patients (16%), 18% and 9% of VKA and DOAC patients (HR 1.95; 95% CI 1.19–3.22, p = 0.008). The rate of death at 30 days was similar in VKA and DOAC patients with intracranial hemorrhage (26% and 24%; HR 1.05, 95% CI 0.54–2.02) and gastrointestinal bleeding (11% and 7%; HR 1.46, 95% CI 0.57–3.74) and higher in VKA than DOAC patients with other MBs (10% and 3%; HR 3.42, 95% CI 0.78–15.03). Conclusions: Admission for ICH is less frequent for DOAC patients compared with VKA patients. Admission for gastrointestinal MB is more frequent for DOAC as compared to VKA patients. Mortality seems lower in patients with MBs while on DOACs than VKAs but this finding varies across different types of MBs.